Case Study of Inflation and Income of Corn Farmers in Medan Krio Village - Bakhtiar Efendi; Daud Arifin; Alexander Zebua (Proceeding of The International Conference on Economics and Business, 2023)
This case study analysis is to examine the relationship between inflation and the income of corn farmers in Medan Krio village over a period of time. The method used is a descriptive analysis based on a case study study between monetary variables inflation and macroeconomic variables of corn farmer income. The results of descriptive analysis based on theoretical studies and previous research show that inflation has an influence on income so that inflation variables affect the income of corn farmers in the research location, namely Medan Krio village. It is of special concern for the government to continue to support the sustainability of the production process of corn farmers in villages, especially focusing on Medan Krio village as a research location.